2020
DOI: 10.1038/s41436-019-0684-x
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic testing for Parkinson disease: current practice, knowledge, and attitudes among US and Canadian movement disorders specialists

Abstract: Purpose: Genetic testing for Parkinson disease (PD) has not been widely used in clinical practice. In preparation for upcoming precision medicine-designed clinical trials for GBA and LRRK2, we evaluated movement disorders specialists' current practice, knowledge, attitudes, and barriers to genetic testing in PD. Methods: An anonymous questionnaire was sent to movement disorders specialists at 146 Parkinson Study Group (PSG) sites in the United States (n = 131) and Canada (n = 15) to assess their knowledge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 18 publications
1
67
1
1
Order By: Relevance
“…In March 2020, the United States recognized the outbreak of the SARS‐CoV‐2 virus, known as the coronavirus disease 2019 (COVID‐19) pandemic. Prior to the pandemic, there were reports of remote services being implemented and studied in neurology, neurogenetics, and genetic counseling (Achey et al., 2014 ; Alcalay et al., 2020 ; Cohen et al., 2016 ; Ekeland et al., 2010 ; Greenberg et al., 2020 ; Hilgart et al., 2012 ; Kane & Gillis, 2018 ; Mitchell & Demiris, 2005 ). Remote services have been described by the terms teleneurology, telemedicine, and telehealth (Achey et al., 2014 ; Alani, 2020 ; Alcalay et al., 2020 ; Cheney, 2020 ; Eberly et al., 2020 ; Ekeland et al., 2010 ; Kane & Gillis, 2018 ; Parmanto et al., 2016 ; Spindler et al., 2020 ; Wilkinson et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In March 2020, the United States recognized the outbreak of the SARS‐CoV‐2 virus, known as the coronavirus disease 2019 (COVID‐19) pandemic. Prior to the pandemic, there were reports of remote services being implemented and studied in neurology, neurogenetics, and genetic counseling (Achey et al., 2014 ; Alcalay et al., 2020 ; Cohen et al., 2016 ; Ekeland et al., 2010 ; Greenberg et al., 2020 ; Hilgart et al., 2012 ; Kane & Gillis, 2018 ; Mitchell & Demiris, 2005 ). Remote services have been described by the terms teleneurology, telemedicine, and telehealth (Achey et al., 2014 ; Alani, 2020 ; Alcalay et al., 2020 ; Cheney, 2020 ; Eberly et al., 2020 ; Ekeland et al., 2010 ; Kane & Gillis, 2018 ; Parmanto et al., 2016 ; Spindler et al., 2020 ; Wilkinson et al., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the pandemic, there were reports of remote services being implemented and studied in neurology, neurogenetics, and genetic counseling (Achey et al., 2014 ; Alcalay et al., 2020 ; Cohen et al., 2016 ; Ekeland et al., 2010 ; Greenberg et al., 2020 ; Hilgart et al., 2012 ; Kane & Gillis, 2018 ; Mitchell & Demiris, 2005 ). Remote services have been described by the terms teleneurology, telemedicine, and telehealth (Achey et al., 2014 ; Alani, 2020 ; Alcalay et al., 2020 ; Cheney, 2020 ; Eberly et al., 2020 ; Ekeland et al., 2010 ; Kane & Gillis, 2018 ; Parmanto et al., 2016 ; Spindler et al., 2020 ; Wilkinson et al., 2016 ). In genetic counseling, the remote service delivery models have been defined as either ‘telephone genetic counseling’ for a session about a new indication conducted entirely via telephone, or ‘telegenetics’ for a web‐based videoconferencing or telemedicine genetic counseling visit (Cohen et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has found that movement disorder specialists are not widely offering genetic testing to their patients with PD. A key reason cited by neurologists for this reduced utilization was the confusion surrounding genetic testing [16]. Further, the impact of negative results on test utility and interpretation for genetic counseling are markedly different if five versus more than 60 genes are tested.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] Besides potential barriers for reimbursement, many neurologists feel poorly prepared to provide counseling to patients regarding results. 24 In addition, other issues that may arise from comprehensive testing using genome sequencing have not been fully explored, such as disclosure of genetic risk scores or potential discovery of medically actionable findings unrelated to PD diagnosis. In order to address these gaps, it is essential to document not only the spectrum of genetic findings that would be expected in clinical practice, but also the possible reactions of patients to such results.…”
Section: Introductionmentioning
confidence: 99%